Toxicity profiling of gold and iron oxide nanoparticles as a radiographic contrast media / Muhamad Idham Mohamed - Mohamed, Muhamad Idham (2015)
Exponential growth of nanotechnology has led to a tremendous research and development to exploit their novel properties in various fields including diagnostic imaging. To date, iodine has been clinically used as a radiographic contrast medium. However, raising concern of iodine threats lead to an exploration of new contrast media with lower toxic level. In animal modeling study, gold nanoparticles (GNPs) and iron oxide nanoparticles (IONPs) have been assessed for toxicity properties as compared to conventional iodine. Nanotoxicities were assessed in liver and kidney tissues by hematology and biochemical analyses, ROS and MDA production, histology and ultrastructural evaluation, and followed by apoptosis and DNA damage induction. The hematological and biochemical analyses revealed that most of the parameters were significantly increased in iodine-administered group compared to those in control group and NPs-administered groups (p < 0.05). ROS and MDA production were recorded as significantly reduced in NPs-administered group (p < 0.05). Histological and ultrastructural evaluations showed that there were significant alteration in liver and kidney tissues of iodine-administered rats (p < 0.05) compared to control and NPs groups. Apoptosis was not detected in both NPs-administered groups while it was observed in iodine-administered group. Induction of DNA damage by comet assay was significantly observed in iodine-administered group compared to other groups {p < 0.05). The present study documented that intravenous administration of GNPs and IONPs did not induce appreciable toxicity compared to iodine, hence postulated that GNPs and IONPs could be potentially utilized in radiographic imaging.